1986
DOI: 10.1021/ja00270a063
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of hemin-catalyzed alkene epoxidation. The effect of catalyst on the regiochemistry of epoxidation

Abstract: The blue copper proteins have been the focus of many spectroscopic and structural studies,1 with much of the interest centering on the nature of the copper site. X-ray crystallographic results have previously been reported for two single-copper proteins, plastocyanin and azurin. The structure of the oxidized, Cu(II),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(27 citation statements)
references
References 0 publications
0
24
0
3
Order By: Relevance
“…B is a metallooxetane intermediate. A more detailed description of possible reaction pathways and putative intermediates has been given before both for heme models and heme proteins (11,(35)(36)(37)(38). From these papers, it becomes clear that in many cases the oxygen transfer is a stepwise process, often involving a ferryl oxygen transfer to form the discrete cation intermediate D or radical intermediate E. Also, an intermediate radical-cation C may be involved.…”
Section: Conversions Of the Different Styrene Derivatives By Cip And Mpomentioning
confidence: 99%
See 1 more Smart Citation
“…B is a metallooxetane intermediate. A more detailed description of possible reaction pathways and putative intermediates has been given before both for heme models and heme proteins (11,(35)(36)(37)(38). From these papers, it becomes clear that in many cases the oxygen transfer is a stepwise process, often involving a ferryl oxygen transfer to form the discrete cation intermediate D or radical intermediate E. Also, an intermediate radical-cation C may be involved.…”
Section: Conversions Of the Different Styrene Derivatives By Cip And Mpomentioning
confidence: 99%
“…This is the putative mechanism for CPO in the epoxidation of alkenes, the so-called ferryl-oxygen transfer mechanism (11), comparable with the oxygen transfer mechanism of cytochrome P450. It has also been suggested that electron transfer from the alkene to compound I may occur first, forming a compound II-like species and an intermediate radical cation that can undergo different fates, leading to the formation of epoxides or aldehydes (11,(35)(36)(37)(38).…”
mentioning
confidence: 99%
“…In a typical experiment iron nzeso-tetrakis(2,6-dichloropheny1)porphyrin chloride (4) (8) in CH2C12 was cooled in a CC14 -dry ice bath and the solution saturated with ethylene. Excess iodoso~entafluorobenzene was added and the reaction mixture allowed to warm to room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary experiments on the epoxidation of 1-hexene using 4 and even more electron deficient porphyrins chlorinated on the P-positions of the porphyrin itself (9) show that these less basic porphyrins exhibit less of a tendency towards alkylation. We have proposed that the first step in alkene epoxidation (and N-alkylation) is a one-electron transfer from the olefin to the hemin (8). Since ethylene has a higher oxidation potential than other homologous alkenes the rate of formation of the N-hydroxyethyl complex with the less basic porphyrin could well be slower than its oxidation to the carboxaldehyde.…”
Section: 101520-tetrakis(26-dichloropheny1)porphyrin (8)mentioning
confidence: 99%
“…zu N-alkylierten Porphyrinen [126] oder nach Wasserstoff-oder Alkylwanderungen zu Ketonen oder Aldehyden Bei tiefer Temperatur und in Gegenwart von nucleophilen Axialliganden wird jedoch auch eine konzertierte Sauerstoffubertmgung iiber Metallaoxetane 3 als wahrscheinlich angesehen 146, ti5,121,127,128], zumal kurzlich spektroskopische und chemische Beweise fur die Existenz solcher Intermediate erbracht werden konnten [118]. [120,124]. …”
Section: Erzeugung Der Katalytisch Aktiven Speziesunclassified